A comparative study of ultrasound and thermal processing: Effects on goat milk stability and protein structure - Xiaoxia Chen; Lusha Wei; Yazhou Mao; Aiqing Zhao; Meixue Pu; Yufang Liu; Bini Wang (Journal of Dairy Science)
ABSTRACT: Ultrasonic treatment has been shown to improve the functional properties and quality of proteins; however, the effects of ultrasound on the proteins in goat milk and the quality of goat milk are not clear. In this study, we aimed to analyze the thermal stability of whole, raw goat milk in terms of protein structure aspect. Goat milk was subjected to ultrasound treatments (400 W for 10 min, 500 W for 10 min, and 600 W for 10 min), and untreated and heat-treated samples served as controls. The results demonstrated that ultrasonic treatment led to a more uniform distribution of fat globules and protein particles, reduced agglomeration, and fostered a more compact and ordered protein network structure. Additionally, it enhanced the stability of goat milk. After ultrasonic treatment, the composition and structure of goat milk protein changed. The exposure of more hydrophobic groups enhanced the intermolecular forces, thereby making the protein conformation more stable. These findings indicate that ultrasonic processing not only improved the structure of goat milk proteins but also increased their thermal stability. This study highlights the potential of ultrasonic treatment as an effective method for enhancing the stability and quality of goat milk.